Historical hydroclimatic variability of the Zapalinamé Sierra and water resources for Saltillo, Coahuila - Villanueva Díaz, José; Cerano Paredes, Julián; Constante García, Vicenta; Fulé, Peter Z.; Cornejo Oviedo, Eladio (Instituto de Ecología, A.C., 2016)
The Sierra Zapaliname (SZA) is the most important source of water for Saltillo and neighboring settlements. Population increase is putting pressure on limited water sources, therefore it is necessary to have a better understanding of historical hydroclimate variability for planning the proper use of limited water resources. Tree-ring series were developed for the lower, mid, and upper sections along an altitudinal gradient in SZA. The chronology length was 412 years (1595-2006), 306 years (17002005) , and 603 years (1400-2002), for the lower, mid, and higher elevation, respectively. The lower elevation tree-ring chronology had higher climatic sensitivity to dry periods as compared to those of the mid and upper elevation sections. Intense and extended droughts were detected along the altitudinal gradient in the 1440s to 1450s, 1530s, 1590s, 1640s, 1660s, 1690s, 1710s, 1740s, 1750s, 1760s, 1790s, 1860s, 1890s, 1920s, 1950s, and 2000s, and produced local and regional food shortage and epidemic outbreaks. Severe droughts were detected at frequencies of 100 years followed by mid intensive droughts at 50-year periods. The climatic influence of ENSO in determining hydroclimatic behavior of SZA has not been significant and other circulatory patterns (cold fronts, hurricanes, tropical storms) could better explain the historical climate variability that has characterized this mountain range.